Analisis Kesalahan dalam Menyelesaikan Soal Cerita Sistem Persamaan Linier Dua Variabel Berdasarkan Prosedur Newman ditinjau dari Gaya Belajar Siswa Kelas VIII - Ahmad Talib; Rosidah; Andina Ainayah Naim (Issues in Mathematics Education (IMED), 2022)
This study aims to describe errors in solving two-variable linear equation system story problems based on the Newman procedure in terms of the learning styles of class VIII junior high school students. The type of research used is descriptive qualitative research. By using purposive sampling technique, 3 research subjects were selected, namely one student in each type of learning style, namely visual, auditory, and kinesthetic. The instruments used in data collection were a learning style questionnaire, test questions about a two-variable linear equation system and interview guidelines. Data analysis techniques include data condensation, data presentation, drawing conclusions. The results showed that subjects with visual learning style made mistakes encoding error, subjects with auditory learning style performed processing skills error and encoding error, and subjects with kinesthetic learning styles made mistakes in comprehension error, transformation error, process skills error and enconding error.